Constructing And Destabilizing Ideology In A Media Poster On The Free Nutritious Meal Program (Mbg): A Barthes–Derrida Analysis - Handini Aprillia Ros; Mayang Pipit (International journal of technology and education research, 2026)
This study investigates how meaning and ideology are constructed and contested in a media poster featuring Dr. Media Wahyudi Askar in relation to Indonesia’s Free Nutritious Meal Program (MBG). Employing a qualitative visual discourse analysis, the study integrates Roland Barthes’ semiotic framework and Jacques Derrida’s deconstructive approach to examine how visual political communication shapes public understanding of policy issues. The findings reveal that the poster constructs authority, credibility, and policy legitimacy through interconnected visual and textual signs that operate at the levels of denotation, connotation, and myth. At the same time, a deconstructive reading demonstrates that these meanings are neither fixed nor self-evident but remain dependent on unstable oppositions, exclusions, and alternative interpretations. The study concludes that visual political communication actively participates in the production and negotiation of ideological meanings rather than merely reflecting social reality. By combining semiotics and deconstruction, this research contributes a more comprehensive framework for analyzing contemporary visual discourse and offers insight into how authority, legitimacy, and public knowledge are constructed and challenged in digital media.